EUCLID'S "ELEMENTS" WORK, HIS ADVANTAGES AND DISADVANTAGES (Лучшие интеллектуальные исследования, 2025)
Annotation: In the article The advantages and disadvantages of Euclid's 13-book work "Fundamentals" are studied. These books contain an algorithm for finding the greatest common divisor of two integers and prove that there are infinitely many prime numbers. In the process of teaching high school geometry, it is necessary to rely on different axiom systems to use different textbooks. Therefore, it is extremely important for young teachers to have extensive knowledge of the requirements for the axiomatics of geometry, as well as the ability to use several different axiom systems.